The little Mac book - Williams, Robin 1953- (Peachpit Press, 2010)
Adopting a back-to-the-basics approach, this bestselling little Mac classic has been revised and overhauled to introduce users to Snow Leopard, Apple's newest version of its operating system. In the gentle, friendly, funny style that generations of computer users have come to know and love, author Robin Williams shows readers how to dive in and start working with the Mac and OS X Snow Leopard. This full-color little book walks readers through all of the key new features in Snow Leopard. Using straightforward, jargon-free explanations delivered in logical, easy-to-follow sections, Robin is a new user's personal guide, coaching and encouraging readers as they learn their way around the magic of the Mac.
Print version record
Keywords: Mac OS; Operating systems (Computers); Macintosh (Computer); Systèmes d'exploitation (Ordinateurs); Macintosh (Ordinateur); operating systems